PID Control for a Two-Axis Orientable Solar Panel System - J. Roldán-Mckinley (Scientia Et Technica, 2019)
Orientable solar panel systems (OSPS) greatly improve its performance, based not only on the orientation motion at the right time along the day but also using a good motion strategy to describe that rotation. The control of a two degree-of-freedom OSPS was simulated for a control scheme that combines Proportional, Integral and Derivative actions with a computed torque control inner loop. The latter controller calculates the torques at the joints. Two plants of the dynamic model of the OSPS were evaluated: analytical and Simmechanics. Three case motions were simulated: random, to a sef position, and end-of-the-day cycle. Controller gains were set by using the sustained oscillation Nichols-Ziegler second syntonization method. It was found that in order to save energy along the motion the non-underdamped behavior is required. This is attained by setting the integral component gain to zero. Very small maximum theoretical position errors of the azimuth and elevation position angles suggest that the combination Proportional Derivative combined with Computed Torque Control scheme is satisfactory for controlling the OSPS motion along day.